Categorías sociales y personas en situación de exclusión. Una aproximación desde el País Vasco - Raya Diez, Esther (Cuadernos de Relaciones Laborales, 2006)
During the last twenty five years the social changes gave rise to social exclusion is seen as a new social problem in Western societies. Although several sectors of population are included under the label of «social exclusion», social sciences have not achieved yet to a consensus regarding to what population is included in this universe. In the last years the regulation of norms and programs of social policy related to this sector of population have appeared, however we do not have a sociological answer to the question of who are the socially excluded people. Since social exclusion is a multicausal phenomenon, it is necessary to reach an approach to link different coexisting factors in the same situation, to determine wich is the degree of social exclusion. In this essay we show the methodology used by the Observatory of Processes of Exclusion and Social Incorporation for studying people in situation, or risk, of socially excluding, what allows analysing multifactorial nature of the subject as a study object.